ASSESSMENT OF BLOOD GLUCOSE MANAGEMENT PRACTICES AND THEIR ASSOCIATION WITH CLINICAL OUTCOMES AMONG HOSPITALIZED PATIENTS: A CROSS-SECTIONAL STUDY AT SIR SADIQ ABBASI HOSPITAL, BAHAWALPUR (Journal of Medical & Health Sciences Review, 2025)
Background: Dysregulated blood glucose levels in hospitalized patients are linked to increased morbidity, mortality, and length of stay. Despite evidence-based guidelines, management practices often vary, particularly in resource-constrained hospitals.Objective: To assess current practices of blood glucose management among hospitalized patients and examine their association with selected clinical outcomes at Sir Sadiq Abbasi Hospital, Bahawalpur.Methods: A descriptive cross-sectional study was conducted among 100 inpatients receiving medical or surgical care. Data were collected through structured observation checklists, patient records, and short interviews. Key variables included glucose monitoring frequency, insulin administration practices, diet compliance, and complications. Statistical analysis involved descriptive measures and chi-square tests for associations.Results: Of 100 patients (mean age: 54.3 ± 12.8 years; 56% male), 42% had diabetes. Only 35% received glucose monitoring as per guidelines (≥4 times/day). Insulin administration errors were noted in 18% of cases. Clinical complications such as hypoglycemia (11%) and delayed wound healing (19%) were significantly associated with poor glucose monitoring practices (p < 0.05).Conclusion: The study highlights significant gaps in inpatient glucose management, particularly in monitoring and insulin handling. Addressing these gaps could improve patient safety and outcomes. Training of nursing staff, standardized protocols, and routine audits are recommended to ensure safe glucose control in hospital settings.